2006
DOI: 10.1038/sj.mp.4001778
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage scan in a large bipolar disorder sample from the National Institute of Mental Health genetics initiative suggests putative loci for bipolar disorder, psychosis, suicide, and panic disorder

Abstract: We conducted a 9-cM genome scan in a large bipolar pedigree sample from the National Institute of Mental Health genetics initiative (1060 individuals from 154 multiplex families). We performed parametric and nonparametric analyses using both standard diagnostic models and comorbid conditions thought to identify phenotypic subtypes: psychosis, suicidal behavior, and panic disorder. Our strongest linkage signals (genome-wide significance) were observed on chromosomes 10q25, 10p12, 16q24, 16p13, and 16p12 using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 27 publications
4
94
0
2
Order By: Relevance
“…Of these, chromosomes 2q24 and 1q44 have been implicated in previous studies of BP. A study by Cichon et al 15 showed suggestive evidence of linkage across a broad region on chromosome 2q21-33 and this region was also implicated in Middleton et al 16 On chromosome 1q44, Cheng et al 17 reported a finding at D1S1609, the same marker where our peak occurred. Interestingly, DISC1, which has been the focus of extensive research in both schizophrenia and BP disorder, 18 is approximately 11 Mb away.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Of these, chromosomes 2q24 and 1q44 have been implicated in previous studies of BP. A study by Cichon et al 15 showed suggestive evidence of linkage across a broad region on chromosome 2q21-33 and this region was also implicated in Middleton et al 16 On chromosome 1q44, Cheng et al 17 reported a finding at D1S1609, the same marker where our peak occurred. Interestingly, DISC1, which has been the focus of extensive research in both schizophrenia and BP disorder, 18 is approximately 11 Mb away.…”
Section: Discussionsupporting
confidence: 66%
“…39 That same group studied a separate sample and found genome-wide significant linkage to BP with psychosis on chromosome 16p12. 17 Several of these loci fall within regions that have been implicated in previous studies of BP and schizophrenia. 40 This has led some investigators to propose that psychotic features in BP may reflect an overlap in the etiology of the two disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide victims have increased numbers of alpha-2A adrenergic receptors and mRNA expression in the hippocampus and frontal cortex (Escriba et al, 2004;Garcia-Sevilla et al, 1999;Gonzalez et al, 1994). Moreover, the ADRA2A receptor gene is located on chromosome 10q24-q26, a region that has been linked to SB in genome-wide linkage studies (Cheng et al, 2006). The noradrenergic system is thought to be implicated in aggressive and impulsive behaviors, and enhanced noradrenergic activity may have a role in SB (Oquendo and Mann, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Existen estudios de tamizaje del genoma que utilizan el fenotipo de conducta suicida, observándose la presencia del ligamiento en las regiones cromosomales 2p, 5q, 6q25, 8p, 11q y sugieren ligamiento en 1q4, 2q2, 4p16, 8q24, 10q21 y 10q25 (Cheng et al, 2006;Zubenko et al, 2004). Con base en esta evidencia, los estudios con genes que se encuentran en estas regiones son determinantes en la etiología de la conducta suicida.…”
Section: Genética Molecular De La Conducta Suicidaunclassified
“…Con base en esta evidencia, los estudios con genes que se encuentran en estas regiones son determinantes en la etiología de la conducta suicida. En este mismo sentido, algunos genes que participan en la transmisión de la serotonina como el gen 5HT1B se encuentran en las regiones de ligamiento (Cheng et al, 2006). Una desventaja de los estudios de ligamiento es que no identifican genes de pequeño efecto que de manera aditiva contribuyen al desarrollo de la conducta suicida.…”
Section: Genética Molecular De La Conducta Suicidaunclassified